Peningkatan Hasil Belajar Materi Penyajian Data Dalam Pelajaran Matematika Di Kelas VII-B MTs. Negeri 2 Mojokerto Dengan Metode Resitasi - Mujizatul Ainiyah (Indonesian Journal of Integrated Science and Learning, 2024)
This study began with the very low average mathematics score in class VII-B MTs. Negeri 2 Mojokerto, which was 56.6 and students who achieved learning completion were 17 students or 51.5%. From the analysis of the questions that had been done, the most difficulties experienced by students were students who had difficulty in determining the mean, mode and median, quartile deviation and average deviation from a frequency table. This study aims to improve mathematics learning outcomes about data presentation in class VII-B MTs. Negeri 2 Mojokerto with the recitation method. The subjects of the study were 33 students in class VII-B. The researcher used a classroom action research model. Observations were divided into two learning cycles, each cycle was carried out for 2 meetings. The results of the study concluded that the application of the recitation method can improve mathematics learning outcomes about data presentation. This is based on the results of the study which continued to increase from the first to the last cycle. In the first cycle, an average score of 69 was obtained. Students who had achieved learning completion were 22 students or 66.7%. In the second cycle, the average value was 79.2. Students who had achieved learning completion were 29 students or 87.9%.